Overcoming the Solubility Barrier of Ibuprofen by the Rational Process Design of a Nanocrystal Formulation - Andreas Ouranidis; Nikos Gkampelis; Elisavet Vardaka; Anna Karagianni; Dimitrios Tsiptsios; Ioannis Nikolakakis; Kyriakos Kachrimanis (MDPI AG, 2020)
Wet media milling, coupled with spay drying, is a commonly proposed formulation strategy for the production and solidification of nanosuspensions in order to overcome the solubility barrier of BCS Class II substances. However, the application of mechanically and thermally intensive processes is not straightforward in the cases of ductile and/or low melting point substances that may additionally be susceptible to eutectic formation. Using ibuprofen (IBU) as a model drug with non-favorable mechanical and melting properties, we attempt to rationalize nanocrystal formulation and manufacturing in an integrated approach by implementing Quality by Design (QbD) methodology, particle informatics techniques and computationally assisted process design. Wet media milling was performed in the presence of different stabilizers and co-milling agents, and the nanosuspensions were solidified by spray-drying. The effects of key process parameters (bead diameter, milling time and rotational speed) and formulation variables (stabilizer type and drug/stabilizer ratio) on the critical quality attributes (CQAs), i.e., Z-average size, polydispersity index (PDI), ζ-potential and redispersibility of spray-dried nanosuspensions were evaluated, while possible correlations between IBU free surface energy and stabilizer effectiveness were studied. The fracture mechanism and surface stabilization of IBU were investigated by computer simulation of the molecular interactions at the crystal lattice level. As a further step, process design accounting for mass-energy balances and predictive thermodynamic models were constructed to scale-up and optimize the design space. Contemplating several limitations, our multilevel approach offers insights on the mechanistic pathway applicable to the substances featuring thermosensitivity and eutectic tendency.